Variasi Konsentrasi Inhibitor Kulit Bawang Merah 0 PPM, 100 PPM, 200 PPM, dan 300 PPM terhadap Nilai Laju Korosi Pipa Radiator (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2026)
This study investigates the effect of adding onion peel extract as a corrosion inhibitor on the corrosion rate and hardness of radiator pipes. The research employed an experimental method with inhibitor concentrations of 0 ppm, 100 ppm, 200 ppm, and 300 ppm. Corrosion rate testing was conducted using electrochemical methods, while hardness was measured using the Vickers method. The findings reveal that the addition of onion peel extract at a concentration of 300 ppm significantly reduced the corrosion rate to 0.081 mmpy, achieving an inhibition efficiency of 56.45%. Furthermore, the same concentration enhanced the surface hardness of radiator pipes to 255.403 Kgf/mm². These results demonstrate that onion peel extract has strong potential as an eco-friendly organic corrosion inhibitor. Its dual function in reducing corrosion and improving mechanical properties highlights its applicability in radiator pipe protection and sustainable engineering practices. The study contributes to the development of natural inhibitors as alternatives to synthetic chemicals, aligning with environmental preservation efforts and advancing green technology in material protection.